2010
DOI: 10.1007/s11747-010-0210-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiple emotional contagions in service encounters

Abstract: This paper investigates the dynamic impact of multiple sequential emotional displays by employees on customers' negative emotions. Using video-based stimuli to manipulate emotional displays by employees, this study shows the sequential occurrences of negative and positive emotional contagions in service failure and recovery encounters. The results suggest that higher levels of employees' negative emotional displays lead to a greater increase in customers' negative emotions through the process of negative emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 37 publications
6
77
1
4
Order By: Relevance
“…Rather, they can influence those who have direct contact with them, i.e., users who participate in the same discussion threads with employees and/or receive direct responses from employees. In line with prior research [23,37], we propose that positive user sentiment may be enhanced by positive employee sentiment and reduced by negative employee sentiment. Similarly, positive employee sentiment can decrease negative user sentiments, whereas negative employee sentiment can increase them.…”
Section: Employee Communication and User Sentimentsupporting
confidence: 71%
See 1 more Smart Citation
“…Rather, they can influence those who have direct contact with them, i.e., users who participate in the same discussion threads with employees and/or receive direct responses from employees. In line with prior research [23,37], we propose that positive user sentiment may be enhanced by positive employee sentiment and reduced by negative employee sentiment. Similarly, positive employee sentiment can decrease negative user sentiments, whereas negative employee sentiment can increase them.…”
Section: Employee Communication and User Sentimentsupporting
confidence: 71%
“…Prior research in offline contexts has extensively studied how managers and team leaders can regulate their affective displays to influence the affective states of receivers. For example, in the service environment, Du, Fan, and Feng [23] found that positive emotional displays by employees increased the number of positive emotional displays by customers, as well as reduced their negative emotional displays. Employees operating on the internet (whether considered managers or moderators of the community) have direct contact with online users.…”
Section: Employee Communication and User Sentimentmentioning
confidence: 99%
“…This measure includes two items to assess task orientation (α = .90) and another two items to capture recreational orientation (α = .80). Finally, the respondents indicated whether salespersons were present or not, assessed the perceived realism of the described scenarios with two items (α = .72) taken from Du et al (2011), and provided their age and gender before completing an open-ended suspicion probe question.…”
Section: Methodsmentioning
confidence: 99%
“…Realism evaluation (Du et al 2011) .72 I think there are similar shopping situations in everyday life.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Az érzelemát-vitel azt fejezi ki, hogy az emberek hajlamosak egymás érzelmi állapotait visszatükrözni, anélkül, hogy ez tudatosulna bennük (Hatfield et al, 1994). Az érzelemát-vitelt több empirikus kutatásban is igazolták (Bailey et al, 2001;Pugh, 2001;Du et al, 2011). Az eredmények azt mutatják, hogy az alkalmazottak pozitív érzelmi megnyilvánulása befolyásolja a fogyasztók érzelmeit, és végső soron kihat a szolgáltatással való elégedettsé-gükre.…”
Section: Kulcsszavakunclassified